Dynamic Zinc Accumulation and Contributions of Pre- and/or Post-Silking Zinc Uptake to Grain Zinc of Maize as Affected by Nitrogen Supply - Xue, Yan-Fang; Yue, Shan-Chao; Liu, Dun-Yi; Zhang, Wei; Chen, Xin-Ping; Zou, Chun-Qin (Frontiers in Plant Science, 2019)
Nitrogen (N) supply could improve the grain yield of maize, which is of great importance to provide calories and nutrients in the diets of both humans and animals. Field experiments were conducted in 2009 and 2010 to investigate dynamic zinc (Zn) accumulation and the pre-silking and post-silking Zn uptake and their contributions to grain Zn accumulation of maize with different N supply under field conditions. Results showed that only 1.2% to 39.4% of grain Zn accumulation derived from pre-silking Zn uptake, with Zn remobilization being negatively affected by increasing N supply. However, post-silking Zn uptake (0.8–2.3 mg plant–1) and its substantial contribution to grain Zn accumulation (60.6%–98.8%) were progressively enhanced with the increasing N supply. Furthermore, grain Zn concentration was positively associated with grain N concentration (r = 0.752***), post-silking N uptake (r = 0.695***), and post-silking Zn uptake (r = 738***). A significant positive relationship was also found between post-silking uptake of N and Zn (r = 0.775***). These results suggest that N nutrition is a critical factor for shoot Zn uptake and its allocation to maize grain. Dry weight, and N and Zn concentration of grain and straw were significantly enhanced with the increasing N from “no N” to “optimal N” supply (150 kg N ha−1 in 2009 and 105 kg N ha−1 in 2010), but further increasing N supply (250 kg N ha−1) generally resulted in a non-significant increase in both cropping seasons. During the grain development, N supply also generally tended to improve grain N and Zn concentrations, but decrease phosphorus (P) concentration and the molar ratio of P to Zn compared with null N application. These results suggest that grain Zn accumulation mainly originates from post-silking Zn uptake. Applying N at optimal rates ensures better shoot Zn nutrition and contributes to post-silking Zn uptake, maintaining higher grain Zn availability by decreasing the molar ratio of P to Zn, and resulting in benefits to human nutrition.